Makna Eksoteris dan Esoteris Agama dalam Sikap Keberagamaan Eksklusif dan Inklusif - Basyir, Kunawi (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2018)
Within the last decades, known to us as the century of spirituality, the world civilization has been murkily colored by the darkness and it has been caused by our sharp different view when we try to understand the meaning of religion including Islam. This has led to the absence of ?a bowl? of peace, justice, and equality for every person to freely express his or her socio-religious activities. To the exclusivists, for instance, Islam is blindly viewed as the sole religion that possesses absolute value of truth (absolutism). Consequently, this group sees that other religions possess no truth and, therefore, they must be obliterated. This group sees isl?m as a term to reject religious pluralism in Indonesia. On the other side, the inclusivists consider the truth of isl?m as the universal truth. In this regard, they argue that the truth of Islam as a religion is the sole truth, but the truth of isl?m cannot be monopolized only by certain religion. They further argue that other religions may also possess the truth of isl?m. Paying close attention to such different understanding of isl?m, this article attempts to re-read and re-analyze it from socio-cultural approach (or strictly speaking from philoso-phical and theological point of view).